Dynamics of Growth, Poverty, and Inequality in Pakistan (The Pakistan Development Review, 1999)
The relationship between growth, inequality, and poverty has been a moot point. On the one hand growth is considered central or the best course to reduce poverty (e.g. World Development Report 1990) with the preconditions that access to education, health, and social services are available to all by means of other policies. On the other hand, there is a realisation that growth, inequality, and poverty relations are non-linear, complex, and path dependent in their dynamics. An important point made in this context by Kuznets (1955) was the empirical finding of an inverted U (arch) shape relationship between growth and inequality which suggested that the inequality would increase with growth in the beginning, but will decline at higher levels of growth as the benefits of growth trickle down to lower income strata. This argument has been debated since then in the literature with empirical support gathered for and against this hypothesis. Recent theoretical literature on the issue tries to find the micro-foundations of the dynamical relations between these three variables (see for example, proceedings of the 5th ABCDE Annual (World) Bank Conference on Development Economics).